Adjustment of Cell Adhesion on Polyurethane Structures via Control of the Hard/Soft Segment Ratio. Issue 5 (20th March 2020) - Lutzweiler, Gaëtan; Barthes, Julien; Vrana, Nihal Engin; Rawiso, Michel; Louis, Benoît; Mayingi, Josselin; Carre, Albane; Drenckhan, Wiebke; Schaaf, Pierre
Abstract: Creating substrates with a similar composition that can either prevent or promote cell adhesion is still a challenging feat. Here, it is shown that a strikingly simple method of tuning the amount of hard segments or isocyanate index (NCOind ) of a polyurethane (PU) film allows to modulate cell adhesiveness. PU films are synthesized with NCOind of 75, 100, 200, 300 and 400 corresponding to ratios of isocyanate to hydroxyl functions of 0.75, 1, 2, 3, 4, respectively. The adhesive capacity of NIH 3T3 fibroblasts (3T3) and Wharton's jelly mesenchymal stem cells (WJMSCs) are dependent on the NCOind . For NCOind below 300, no cell adhesion can be observed regardless of the cell type, whereas for NCOind of 300 and 400 cells adhere to the PU surface. WAXS and small angle X‐ray scattering (SAXS) studies reveal that variations of NCOind allows to modulate the phase separation in PU films. Porod's law shows that for NCOind of 300 and 400, the hard–soft segment interface is sharp. Conversely, samples with smaller NCOind present diffuse interfaces. Hence, the morphology of the interface between hard and soft domains appears to be a critical feature that correlates with the adhesion capacity of cells. Abstract : Polyurethane (PU) films synthesized with various isocyanate indexes (NCOind) allow to modulate cell adhesion through the phase separation of PU's microstructure. For NCOind <300, the soft/hard segment interface is diffuse, preventing cell attachment. Conversely, above 300, cells are adherent. Therefore, NCOind is an easy way to tailor the adhesive properties of PU through the nature of the soft/hard segment interface.